Body image concern among Australian adolescent girls: The role of body comparisons with models and peers - Carey, Renee; Donaghue, N.; Broderick, P. (2014)
This study investigated the potential mediating roles of body comparisons with peers and models in the relationship between the internalization of thinness norms and body image concern. A total of 224 Western Australian girls aged 14-15 completed questionnaires assessing their endorsement of thinness norms, body image concerns, and frequency of body comparisons with peers and with models. Both targets of body comparisons were found to significantly mediate the relationship between the endorsement of thinness norms and body image concern, with body comparison with peers a stronger mediator than comparison with models. These findings show that body comparison with peers, in particular, plays a significant role in the experience of body image concerns among adolescent girls, and should be given a higher profile in programs designed to prevent or reduce body image concern. © 2013 Elsevier Ltd.